1989
DOI: 10.1111/j.1365-3091.1989.tb00820.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ acoustic measurements of marine gravel threshold and transport

Abstract: Measurements of the nearbed turbulent current flow and the bedload transport of marine gravel have been made over three tidal cycles. The turbulence in the bottom boundary layer was measured using two electromagnetic current meters, and the gravel transport was measured using a passive acoustic system which monitored the interparticle collision noise of locally mobile material. Visual estimates of bedload were also obtained with an underwater TV camera. The acoustic technique, unlike a conventional bedload sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
71
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 17 publications
11
71
1
Order By: Relevance
“…Nakagawa and Nezu (1978) and Grass (1971Grass ( , 1982 have shown that the sweep event above the channel bed is more responsible for transfer of momentum into the boundary layer than the ejection event. In addition, Nakagawa and Nezu (1978), Thorne et al (1989), and Keshavarzy and Ball (1995) indicated that the sweep and ejection events occur more frequently than the outward interaction (quadrant I) and inward interaction (quadrant III) events. Williams (1990) and Thorne et al (1989) showed that sediment entrainment occurs most frequently during sweep events and only occasionally during outward interaction events, whereas transport of suspended sediment depends primarily on the ejection event.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakagawa and Nezu (1978) and Grass (1971Grass ( , 1982 have shown that the sweep event above the channel bed is more responsible for transfer of momentum into the boundary layer than the ejection event. In addition, Nakagawa and Nezu (1978), Thorne et al (1989), and Keshavarzy and Ball (1995) indicated that the sweep and ejection events occur more frequently than the outward interaction (quadrant I) and inward interaction (quadrant III) events. Williams (1990) and Thorne et al (1989) showed that sediment entrainment occurs most frequently during sweep events and only occasionally during outward interaction events, whereas transport of suspended sediment depends primarily on the ejection event.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Nakagawa and Nezu (1978), Thorne et al (1989), and Keshavarzy and Ball (1995) indicated that the sweep and ejection events occur more frequently than the outward interaction (quadrant I) and inward interaction (quadrant III) events. Williams (1990) and Thorne et al (1989) showed that sediment entrainment occurs most frequently during sweep events and only occasionally during outward interaction events, whereas transport of suspended sediment depends primarily on the ejection event. Additionally, Keshavarzy and Ball (1995) have shown that the magnitude of the instantaneous shear stress in a sweep event is greater than outward and inward interaction events.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sediment transport is episodic, with short periods of high transport and long periods of relatively feeble or no transport. Thorne et al (1989) observed that the upward high-speed fluid streaks (known as outward interactions) play an important role on sediment entrainment. It is the instantaneous increase in streamwise velocity fluctuations that generate excess bed shear stresses, governing entrainment processes.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of sweep and ejection events has been found to be more important than outward and inward interactions. Additionally, sweep and ejection events occur more frequently than outward and inward interactions (Nakagwa and Nezu, 1978;Thorne et al, 1989;Keshavarzi and Ball, 1997) with the average magnitude of the shear stress during a sweep event being much higher than the time averaged shear stress (Keshavarzi and Ball, 1997). A number of studies, for example, Offen and Kline (1975) and Papanicolaou et al (2002) investigated the characteristics of the bursting process and its effect on particle motion.…”
Section: A Keshavarzi Et Al: Frequency Pattern Of Turbulent Flow Anmentioning
confidence: 99%
“…Four alternative types of bursting events have been identified with each of these types having different effects on the mode and rate of sediment transport (Bridge and Bennett, 1992). Particle entrainment from the bed is closely correlated to the sweep and ejection events (Thorne et al, 1989;Nelson et al, 1995;Drake et al, 1988;Nakagwa and Nezu, 1978;Grass, 1971;Ball, 1997, 1999). The contribution of sweep and ejection events has been found to be more important than outward and inward interactions.…”
Section: A Keshavarzi Et Al: Frequency Pattern Of Turbulent Flow Anmentioning
confidence: 99%